Mass spectrometric study of intermolecular interactions between the artemisinin-type agents and nucleobases - Pashynska, V. A. (Biophysical Bulletin, 2009)
Artemisinin-type agents are well known as effective antimalarial medicines and recently their anticancer activity was reported, however, there is a lack of investigations on the molecular mechanisms of antitumor activity of artemisinin and its derivatives. This study is aimed at examining the mechanisms of artemisinin-type agents’ anticancer activity. DNA as the carrier of genetic information is one of the major targets for antitumor drug effect and nucleic acids are also suggested as molecular targets of artemisinin action in cancer cells. Biologically significant intermolecular interactions of artemisinin and dihydroartemisinin with some purine and pyrimidine nucleobases were studied by means of testing the drug-nitrogen base mixtures by electrospray ionization mass spectrometry. The peaks of stable noncovalent complexes of the artemisinin-type drug with Ade, Cyt, and mThy were registered in the mass spectra. Comparison of the relative abundances of the peaks of the drug-nucleobase complexes for purine and pyrimidine nitrogen bases was performed. The spectra analysis allowed us to conclude that an effect of the complexation process depends on the structural peculiarities of the drugs and nucleobase molecules. The experimental data and features of the molecular structure of the drugs and nucleobases testify to the suggestion that noncovalent complexes of the artemisinin-type agents and nitrogen bases are stabilized by van der Waals forces and hydrogen bonds between the functional groups of the interacting molecules. Formation of the supramolecular complexes of the artemisinin-type drugs and nucleobases is considered as a possible molecular mechanism of anticancer activity of the studied antimalarial agents. The obtained results demonstrate the great potential of the electrospray ionization mass spectrometry method in the study of the artemisinin-type agents and their intermolecular interactions related to the mechanisms of the drug’s biological activity.